IMPACT OF WAREHOUSE STATUS CATEGORY AND KEY PERFORMANCE INDICATOR COMPATIBILITY FOR WAREHOUSE MANAGEMENT PERFORMANCE AT PT. DHL SUPPLY CHAIN INDONESIA - Rini Mardikawanty; Dadang Surya Kencana; Sausan Mahmudah (POLITEKNIK LP3I JAKARTA, 2026)
DHL Supply Chain Indonesia is one of the largest companies engaged in logistics and warehousing services that collaborates with several customers, one of which is PT. X. This study was conducted due to the trend of KPI fulfillment that remained below target, indicating the need for further research regarding warehouse management performance. This research aims to determine the effect of warehouse status categories based on the Warehouse Check-Up perspective and the compatibility of Key Performance Indicators (KPI) on warehouse management performance at PT. DHL Supply Chain Indonesia. The research method used was descriptive quantitative based on interview results using audit checklists and questionnaire distribution data. Questionnaire data were tested using instrument tests (validity and reliability), classical assumption tests (normality, heteroscedasticity, multicollinearity, and linearity tests), multiple regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination analysis. Based on the tests conducted, it can be concluded that the influence of warehouse status categories based on the Warehouse Check-Up perspective on warehouse management performance is 0.128 or 12.8%. Meanwhile, the influence of KPI compatibility on warehouse management performance is 1.004 or 100%. Furthermore, the simultaneous influence of warehouse status categories and KPI compatibility on warehouse management performance is 0.706 or 70.6%, indicating a strong relationship level.